Kartapoli: APE Dalam Meningkatkan Literasi Moral Anak Rusunawa Ciseureuh Kabupaten Purwakarta - Hisny Fajrussalam; Sofyan Iskandar; Wina Mustikaati; Audrey Rosdiana Putri; Indah Amalia Putri (CV. Multi Kreasi Media, 2023)
This Community Service (PkM) was carried out in Rusunawa Ciseureuh, Purwakarta Regency. The problem faced by partners is the moral quality of children which is fairly concerning. This problem is caused by several factors such as: 1) the available facilities are not used for positive activities for children; 2) parents who are busy working so they rarely spend time with children; and 3) children who often play gadgets so that they are affected by bad content on the internet. This PkM aims to find alternatives to the problems faced by partners, namely the Rusunawa Ciseureuh community so that the moral quality of children can be better formed. This method of implementing PkM is carried out through 3 stages, namely: 1) preparation; 2) implementation; and 3) evaluation. The things produced or achieved from this PkM are: 1) the moral quality of children who have improved to be good and very good after service activities; and 2) the response of parents who are very supportive and enthusiastic to service activities.